A Study on the Relationship Between Transactional Distance, Student Involvement, and Curriculum Satisfaction in a Flipped Class Model: A Case Study in Guilin, Guangxi Province of China (Lex localis - Journal of Local Self-Government, 2025)
The Flipped Class Model (FCM) model has gained increasing popularity in higher education, enabling educators and institutions to address the challenges of distance and blended learning. This study explores the correlation between transactional distance, student involvement, and curriculum satisfaction in a flipped piano education classroom in Guilin, Guangxi of China. Additionally, it examines the impact of students' perceptions of transactional distance on their learning experience. The study employs Structural Equation Modeling (SEM) for path analysis. Data were collected from 69 female and 51 male students in a public university in Guilin. Three established measurement tools were used to assess the relationships among transactional distance perception, student involvement, and curriculum satisfaction. The study investigates five sub-dimensions of transactional distance e—interaction between students and the interface, content, teachers, peers, and the learning environment—to evaluate how these factors influence participation and satisfaction. The results indicate a significant positive correlation between students' perceptions of transactional distance and their involvement and curriculum satisfaction. Specifically, each of the five sub-dimensions of transactional distance positively influences student involvement and satisfaction. These findings provide empirical evidence supporting the crucial role of transactional distance in flipped classroom teaching. This study offers valuable insights for educators and curriculum designers, emphasizing that optimizing students' perceptions of transactional distance can enhance their involvement and satisfaction, thereby improving overall teaching effectiveness. This is particularly relevant in the design of Flipped Class Model, where promoting effective interaction can significantly enhance the students' learning experience.